Energy impoverishment and burns: The case for an expedited, safe and inclusive energy transition in South Africa - Van Niekerk, Ashley; Kimemia, David; Annegarn, Harold; Seedat, Mohamed (South African Journal of Science, 2022)
Energy poverty is the constrained access to modern forms of energy. In South Africa, energy impoverished communities are dependent on a mixture of solid fuels (e.g. wood or coal) and hydrocarbons such as paraffin. These, especially paraffin use, are associated with significant negative health outcomes, particularly burns due to accidental fires and spillages, but also paraffin ingestion, and toxic fume inhalation. The energy-poor furthermore suffer disproportionate long-term social, economic and psychological impacts that entrench their impoverished conditions. There is both international and national recognition of these adverse effects of energy poverty and that the universal access to safe and sustainable energy is crucial for the attainment of health and other global social, economic and well-being goals. South Africa is called on to expedite access to modern energy usage, through the enactment of a substantive policy on the provision of safe, clean and affordable energy for energy-impoverished communities and households.